Blood Gene Expression and Vascular Function Biomarkers in Professional Saturation Diving - Kiboub, Fatima Z.; Møllerløkken, Andreas; Hjelde, Astrid; Flatberg, Arnar; Loennechen, Øyvind; Eftedal, Ingrid (Frontiers in Physiology, 2018)
Saturation diving is an established way to conduct subsea operations with human intervention. While working, the divers must acclimatize to the hyperbaric environments. In this study, genome-wide gene expression and selected plasma biomarkers for vascular function were investigated. We also examined whether antioxidant vitamin supplements affected the outcome. The study included 20 male professional divers, 13 of whom took vitamin C and E supplements in doses of 1,000 and 30 mg daily during saturation periods that lasted 7-14 days. The dives were done in a heliox atmosphere with 40 kPa oxygen partial pressure (ppO2) to a depth of 100-115 meters of sea-water (msw), from which the divers performed in-water work excursions to a maximum depth of 125 msw with 60 kPa ppO2. Venous blood was collected immediately before and after saturation. Following gene expression profiling, post-saturation gene activity changes were analyzed. Protein biomarkers for inflammation, endothelial function, and fibrinolysis: Il-6, CRP, ICAM-1, fibrinogen, and PAI-1, were measured in plasma. Post-saturation gene expression changes indicated acclimatization to elevated ppO2 by extensive downregulation of factors involved in blood oxygen transport, including heme, hemoglobin, and erythrocytes. Immune activity and inflammatory signaling were upregulated. The antioxidant vitamin supplements had no effect on post-saturation gene expression profiles or plasma biomarkers, implying that the divers preserved their homeostasis through their own antioxidant defenses.